2005
DOI: 10.1128/jb.187.21.7193-7203.2005
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Coexistence betweenStreptococcus mutansandStreptococcus sanguinisin the Dental Biofilm

Abstract: The human mucosal surface is colonized by the indigenous microflora, which normally maintains an ecological balance among different species. Certain environmental or biological factors, however, may trigger disruption of this balance, leading to microbial diseases. In this study, we used two oral bacterial species, Streptococcus mutans and Streptococcus sanguinis (formerly S. sanguis), as a model to probe the possible mechanisms of competition/coexistence between different species which occupy the same ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
431
1
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(465 citation statements)
references
References 40 publications
19
431
1
14
Order By: Relevance
“…Early colonization with S. sanguinis is significantly correlated with a delay in colonization by S. mutans. After S. mutans colonization, the levels of S. sanguinis decrease (Caufield et al, 2000;Kreth et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early colonization with S. sanguinis is significantly correlated with a delay in colonization by S. mutans. After S. mutans colonization, the levels of S. sanguinis decrease (Caufield et al, 2000;Kreth et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Early colonization with S. sanguinis is significantly correlated with a delay in colonization by S. mutans. After S. mutans colonization, the levels of S. sanguinis decrease (Caufield et al, 2000;Kreth et al, 2005).Several other studies have focused on the in vitro relationship between S. sanguinis and some of the periodontal pathogens. Hillman et al (1985) showed that, in samples from oral sites where S. sanguinis was detected, Tannerella forsythia was present in 1 % of the cases, and in samples where S. sanguinis was not detected, Tannerella forsythia was present in 10 % of the oral sites.…”
mentioning
confidence: 99%
“…How the two species use AI-2 to effectively compete to increase their relative abundance in these dual-species biofilms is, at present, unknown. Competitive biofilm interactions are known to occur between streptococci via the production of bacteriocins (Streptococcus mutans) and hydrogen peroxide (Streptococcus sanguis) (Kreth et al, 2005) but not as a function of AI-2 cell-cell signalling and/ or bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…S. sanguinis competes with other bacteria by producing a bacteriocin or excreting hydrogen peroxide to trigger the lysis of competitors during initial colonization (Kreth et al, 2008). Several investigators have shown that S. sanguinis can play an antagonistic role against Streptococcus mutans colonization, and early colonization of S. sanguinis is associated with delayed colonization of S. mutans in children (Kreth et al, 2005). Similarly, S. gordonii can also excrete hydrogen peroxide, but the present studies showed no inhibition of S. mutans by S. gordonii (Kreth et al, 2008;Tanzer et al, 2012).…”
Section: Oral Streptococci Succession Associated With S-eccmentioning
confidence: 99%
“…Because of their genetic similarity, the oral streptococci have similar metabolic activities, and multiple species can compete for the ecological niche on the saliva-coated tooth surface. The early colonists to the niche can then produce antimicrobial compounds, such as bacteriocins and hydrogen peroxide, to affect other related species (Kreth et al, 2005;Nes et al, 2007). Moreover, in the cariogenic plaque, other cariesassociated species such as Bifidobacteria and Lactobacillus might also be retained by physical or metabolic interactions with streptococci (Hojo et al, 2009).…”
Section: Oral Streptococci Succession Associated With S-eccmentioning
confidence: 99%